1992
DOI: 10.1088/0953-4075/25/15/009
|View full text |Cite
|
Sign up to set email alerts
|

Competition between radiative and non-radiative decay processes in triply-excited 3131'nl" and doubly-excited 2lnl' states in nitrogen ions

Abstract: Results are presented for radiative and non-radiative decay rates for 3l3l'nl' states in N4+ and 2lnl' states in N5+ in a single configuration as well as in a CI approximation. It is found that while radiative stabilization is negligible for the triply-excited states, it is important for the doubly-excited states with n)6. These results are used to interpret multiple charge-exchange experiments in nitrogen by Benoit-Cattin et al. (1988). The reasons for the difference between the doubly- and triply-excited sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Theoretical investigations of multiply excited states are essentially absent except for the calculations of radiative and nonradiative decay rates in triply excited (3l, 31',nl") N4+ by Vaeck and Hansen [33].…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical investigations of multiply excited states are essentially absent except for the calculations of radiative and nonradiative decay rates in triply excited (3l, 31',nl") N4+ by Vaeck and Hansen [33].…”
Section: Resultsmentioning
confidence: 99%
“…In this Letter, we point out that the decay properties of such states can be expected to be different from the familiar behavior of doubly excited series. This is important, for example, in trying to untangle the competition between radiative and nonradiative decay for such states [9,10].…”
Section: Department Of Physics and Astronomy University Of Amsterdammentioning
confidence: 99%
“…However, in the present context it is fortunate that the radiative decay rate for a transition 2pne -+ lsne is very large compared to the probability for autoionization when the Rydberg electron has a high n or e value. For 2pne states in et (van der Hart and Hansen 1993a) and in Ns+ (Vaeck and Hansen 1992) it has been found that the radiative decay rates are larger than the autoionization rates for all terms already for n less than 10 and generally the mixing between 2pne and 2sne' is so large in a two-electron atom, due to the degeneracy between the hydrogenic 2s and 2p states, that the same will apply to most 2ene' states. Similarly, for the 3ene' states the weight of the 3pne component in the eigenvector is often large enough to allow the direct decay to a Isne state.…”
Section: Radiative Decay Rates and Stabilization Ratiosmentioning
confidence: 99%